Isolation and Characterization of Cellulose Nanofibrils (CNF) from Dates by-Product via Citric Acid Hydrolysis - Aisy, Laaili Azti Rohaadatul; Kemala, Tetty; Suryanegara, Lisman; Purwaningsih, Henny (Science and Technology Indonesia, 2024)
Industrial residues that are not optimally utilized are removed by burning, landfilling, or dumping, which can threaten the environment and health. In fact, part of this agro-industrial waste still has content that has the potential to become raw material for value-added other industries. Dates by-product as residue of the fiber-rich fruit industry have the potential to be a source of nanocellulose. This study aims to obtain nanofibril cellulose (CNF) isolates from dates by-product via citric acid hydrolysis, and investigate the effect of acid concentration on the unknown dates by-product CNF isolate characteristics. Pretreatment such as delignification and bleaching is needed to obtain cellulose isolate with high purity. Furthermore, acid hydrolysis, centrifugation, and sonication are performed to obtain CNF. CNF isolates are characterized by the analysis of particle size distribution, morphology, and crystallinity. Analysis of functional groups and lignocellulose content test confirm that lignin and hemicellulose are degraded during isolation. The particle size distribution measurement shows that the greater the acid concentration, the smaller the CNF size and the better the size uniformity. The morphology of the CNF obtained is net-like fibers. The degree of crystallinity shown decreases with increasing acid concentration. This study revealed that different citric acid concentrations can result in different characteristics of CNF isolates.